Audit Committee, Effectiveness, Bankruptcy Prediction, and Solvency Level Affect Audit Delay - Bramantio Adi Nugroho; Suripto Suripto; Effriyanti Effriyanti (International Journal of Science and Society, 2021)
This study is to gather empirical evidence on the effectiveness of the Audit Committee, bankruptcy forecasts and audit delay solvency. Various manufacturing industries listed on the Indonesian Börse in 2015-2019 were among the population in this study. A selection from 11 companies with 55 observational data was obtained by using the purposeful sampling technique. Testing of hypotheses and the analyzes is conducted using Eviews-10 for the regression of panel data. The findings showed that the efficacy of the audit committee has no significant impact on audit delays, that bankruptcy predictions have a significant impact on the audit delay and that audit delays have a significant impact on the level of solvency.